Developing a Conceptual Framework of Landscape and Hydrology on Tallgrass Prairie:A Critical Zone Approach. Issue 1 (12th October 2017) - Vero, S.E.; Macpherson, G.L.; Sullivan, P.L.; Brookfield, A.E.; Nippert, J.B.; Kirk, M.F.; Datta, S.; Kempton, P.
Abstract : Core Ideas: Konza Prairie is a reference ecosystem for evaluation of current and former grasslands. Hydrologic change includes climatic and geologic factors such as karstification. Future research is needed to expand vadose zone knowledge. Agricultural intensification and urbanization have greatly reduced the extent of tallgrass prairie across North America. To evaluate the impact of these changes, a reference ecosystem of unperturbed prairie is required. The Konza Prairie Biological Station in northeastern Kansas is a long‐term research site at which a critical zone approach has been implemented. Integration of climatic, ecologic, and hydropedologic research to facilitate a comprehensive understanding of the complex environment provides the basis for predicting future aquifer and landscape evolution. We present a conceptual framework of the hydrology underpinning the area that integrates the extensive current and past research and provides a synthesis of the literature to date. The key factors in the hydrologic behavior of Konza Prairie are climate, ecology, vadose zone characteristics and management, and groundwater and bedrock. Significant interactions among these factors include bedrock dissolution driven by cool‐season precipitation and hence a climatic control on the rate of karstification. Soil moisture dynamics are influenced at various timescales due to the short‐ and long‐term effects of prescribed burning on vegetation and on soil physical characteristics. The frequency of burning regimes strongly influences the expansion of woody species in competition with native tallgrasses, with consequent effects on C and N dynamics within the vadose zone. Knowledge gaps exist pertaining to the future of Konza Prairie (a model for US tallgrass prairie)—whether continued karstification will lead to increasingly flashy and dynamic hydrology and whether compositional changes in the vegetation will affect long‐term changes in water balances.